TRADISI MEGALITIK DAN DINAMIKA KEAGAMAAN DI PULAU TERNATE TIDORE (MAKNA PADA MASYARAKAT PENDUKUNGNYA) - Nurachman Iriyanto (Prosiding Seminar Nasional Pakar, 2018)
Megalithic tradition is an ongoing and well-maintained cultural fact to date. The megalithic tradition is not simply about large stones; rather it‟s about the "stones" that receive special treatment through certain rituals. In other words, a meaning is found on the stones, or more precisely, the meaning is given by human who has found and preserved them. There are values on megalithic stones that are collectively embraced and respected by those who believe in them. As a symbol system, the meaning of this tradition undergoes a series of changes in the community as cultural actors for the better life in the future. The present research is aimed to profoundly determine the symbols of megalithic tradition in Ternate Tidore Island as one manifestation of cultural facts mentioned above. The lengthy span of human colonization on both islands has given rise to a meaningful dialectic to the large stones tradition that is known as Jere by the public. The results of field observations find 99 (ninety nine) Jere sites in these two islands. Jere sites which are spread evenly on these two mountain islands possess their own uniqueness, as shown by the spiritual practices and other socio-cultural practices. This research employed phenomenology paradigm, by observing the ongoing socio-cultural lives and apprehending the activities of the tradition actors in defining their world. This approach was used in view of the constancy, harmony, and effects inflicted by Jere tradition on both islands in the established social harmony order. From the exploration process, it is known that Jere tradition is an individual and community awareness towards what they believe to be the embodiment of respect for existence and life. The belief and respect of the people of both islands for the past, the present, and the hope for the future is their perspective on the reality of the natural and supernatural world. Jere is a worship site in the world that aims for the good of life and the achievement of the perfection. Jere is arguably „a people religion’ that reaches out the minds of the people on these two islands and other areas in North Maluku. Jere sites provide positive effects on common life that is ideologically interpreted as life strategies. The institution of Ternate Tidore Palace also seeks to continuously build such dialectic through cultural hegemony with varying socio-humanistic rituals.